APPLICATION OF RIGHTS AND CHARACTERS OF STUDENTS IN BASIC SCHOOL (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The purpose of this study was to determine the application of the rights and character of students in elementary schools. In addition, find out about the Rights and Character of Students in Primary Schools. The data sampling process used in snowball sampling research consisted of principals, teachers, students, school librarians, school guards, and school canteen guards. Whereas for the whole technique the data uses in-depth interviews (in-depth interviews) in the form of structured interviews (structured interviews), in the form of light-clear and disguised analysis (open observation and confidential observation), and documentation. Data analysis in this study through data triangulation techniques with three stages include reduction of data reduction, data presentation, and data verification. The results of this study indicate that with the phenomenon that occurs in Sindang District 1 Elementary School, it can be stated that there are other things or new things that can build students' character not only through the curriculum. The application of children's rights at school can affect the formation of student character. Students who get their rights at school will bring better student characters compared to students who do not get their rights at school. Although the facilities provided by the school both affect children in the classroom are not good but will have a bad impact on students who are not good too. The habits of school residents in the application of children's rights in schools such as providing good facilities, giving attention, providing guidance, not being indifferent to students. Such things will make students more comfortable and suitable for people such as being open, honest, responsible, respectful, legal aware, caring and caring.